(untitled) (The Review of Diabetic Studies, 2025)
Background: Chronic low back pain (CLBP) is a prevalent condition among older adults, leading to functional limitations, reduced quality of life, and increased healthcare utilization. While pharmacological interventions are commonly used, they often carry risks of adverse effects, particularly in the elderly population. Non-pharmacological strategies, including exercise, physiotherapy, education, and nursing-led interventions, are increasingly recognized as safe and effective approaches to manage pain and improve functional mobility. Objective: This systematic review aims to evaluate the effectiveness of physical therapist- and nurse-led non-pharmacological interventions in reducing pain and enhancing functional mobility in older adults with chronic low back pain, based on evidence from randomized controlled trials (RCTs). Methods: A systematic search was conducted in electronic databases including PubMed, Scopus, Cochrane Library, and CINAHL from inception to 2025. RCTs evaluating non-pharmacological interventions delivered by physical therapists or nurses for adults aged 60 years and older with CLBP were included. Studies were screened for eligibility, and data were extracted on intervention type, duration, outcomes related to pain intensity, functional mobility, and adverse events. Quality assessment was performed using the Cochrane Risk of Bias tool. Results: Twenty-two RCTs involving a total of 1,845 older adults met the inclusion criteria. Interventions included structured exercise programs, mobility training, cognitive-behavioral therapy, education on pain management, and nurse-led home exercise support. Across studies, physical therapist-led exercise interventions consistently reduced pain intensity, improved functional mobility, balance, and muscle strength, and enhanced overall quality of life. Nurse-led interventions focusing on patient education, adherence support, and home-based activity promotion demonstrated significant improvements in functional outcomes and patient engagement. Combined physical therapy and nursing interventions showed synergistic effects, with greater reductions in pain and improved functional performance compared to single interventions. Adverse events were minimal, confirming the safety of these non-pharmacological strategies for older adults. Conclusion: Non-pharmacological interventions delivered by physical therapists and nurses are effective and safe strategies for managing pain and enhancing functional mobility in older adults with chronic low back pain. Integrating these approaches into routine care can reduce reliance on pharmacological treatments, improve patient outcomes, and support independent functioning. Future research should investigate long-term effects, cost-effectiveness, and strategies for broader implementation in diverse healthcare settings.